POLISH EXPERIENCE OF USAGE INNOVATIVE METHODS OF TEACHING FOREIGN LANGUAGES - Liudmyla Zagoruiko (Pavlo Tychyna Uman State Pedagogical University, 2017)
The main innovative methods of teaching foreign languages in higher educational institutions in Poland have been described in the article. The meaning of such notions as «method» and «teaching method» has been specified. The factors that contribute to successful foreign language learning in Polish higher educational institutions have been revealed. The necessity of implementation of educational technology in teaching foreign languages has been grounded. Traditional, innovative, information and communication groups of pedagogical techniques have been defined based on the literature study.